Endoscopic ultrasonography‐guided cholecystogastrostomy in patients with unresectable pancreatic cancer using anti‐migratory metal stents: A new approach. Issue 4 (18th September 2013) - Widmer, Jessica; Alvarez, Paloma; Gaidhane, Monica; Paddu, Naveen; Umrania, Hiren; Sharaiha, Reem; Kahaleh, Michel
<x xml:space="preserve">Abstract</x> Cholecystectomy is contraindicated in patients with comorbidities or unresectable cancer. Percutaneous transhepatic gallbladder drainage (PTGBD) is typically offered with response rates ranging from 56% to 100%, but has several risks such as bleeding, pneumothorax, pneumoperitoneum, bile leak, and/or catheter migration. Endoscopic transpapillary gallbladder drainage (ETGD) and endoscopic ultrasound‐guided transmural gallbladder drainage (EUS‐GBD) are alternative endoscopic modalities that have a technical feasibility, efficacy and safety profile comparable with PTGBD. In this report, we present the first case series of transgastric EUS‐GBD with placement of a fully covered self‐expandable metal stent with anti‐migratory fins. In three pancreatic cancercases with acute cholecystitis when ETGD was unsuccessful, there were no bile leaks or procedurally related complications. There were no acute cholecystitis recurrences. In conclusion, EUS‐GBD is a promising, minimally invasive treatment for acute cholecystitis. Additional comparative studies are needed to validate the benefit of this technique.